2008
DOI: 10.1128/aem.00557-08
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Irradiation Can Be Used To Inactivate Bacillus anthracis Spores without Compromising the Sensitivity of Diagnostic Assays

Abstract: The use of Bacillus anthracis as a biological weapon in 2001 heightened awareness of the need for validated methods for the inactivation of B. anthracis spores. This study determined the gamma irradiation dose for inactivating virulent B. anthracis spores in suspension and its effects on real-time PCR and antigen detection assays. Strains representing eight genetic groups of B. anthracis were exposed to gamma radiation, and it was found that subjecting spores at a concentration of 10 7 CFU/ml to a dose of 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
3
26
1
Order By: Relevance
“…High-dose gamma irradiation is known in the literature as a method suitable for reliably inactivating bacterial pathogens (42,43) while leaving the primary protein structures basically intact. Our comparative measurements of pathogenic and nonpathogenic microbial strains essentially confirmed the data in the literature: identification was successful after high-dose gamma irradiation, but irradiation resulted in slightly lower BioTyper log score values (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…High-dose gamma irradiation is known in the literature as a method suitable for reliably inactivating bacterial pathogens (42,43) while leaving the primary protein structures basically intact. Our comparative measurements of pathogenic and nonpathogenic microbial strains essentially confirmed the data in the literature: identification was successful after high-dose gamma irradiation, but irradiation resulted in slightly lower BioTyper log score values (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the known effects of high-dose irradiation on spore viability (16)(17)(18)(19)(20), information about its impact on WGS methods or data quality is limited. Several works have demonstrated the utility of irradiated material for use in immunoassay and PCRbased detection (15)(16)(17), and other investigators have reported the phylogenetic classification of Yersinia pestis strains from highly degraded samples originating from the period of the Black Death (21), which suffer DNA lesions and fragmentation similar to those suffered by irradiated samples.…”
mentioning
confidence: 99%
“…Several works have demonstrated the utility of irradiated material for use in immunoassay and PCRbased detection (15)(16)(17), and other investigators have reported the phylogenetic classification of Yersinia pestis strains from highly degraded samples originating from the period of the Black Death (21), which suffer DNA lesions and fragmentation similar to those suffered by irradiated samples. However, little literature describing the effect of irradiation on DNA within vegetative cells, spores, or naked DNA was available prior to the commencement of this study.…”
mentioning
confidence: 99%
“…The cell pellets were resuspended in 5 ml of sterile phosphate-buffered saline (PBS; 0.01 M, pH 7.4), and the total culture volume was divided into two equal aliquots designated harvest A and harvest B. Harvest A was immediately used as an inoculum to spike the swabs, numbers of CFU/ml were quantified on TSAB plates using standard procedures (9), and the cells were examined by staining and light microscopy (see below). Harvest B underwent a heat-shock treatment (30 min at 65°C) to verify that the inoculum was spore free.…”
Section: Scientific Ethicsmentioning
confidence: 99%
“…This is a highly sensitive and specific assay that was validated for detection of B. anthracis and was successfully used to test hundreds of samples during the 2001 bioterrorism-associated anthrax outbreak. The assay includes three primer and probe sets which target the B. anthracis chromosome and the pXO1 and pXO2 plasmids and has been described in previous reports (9,16). PCR was carried out in triplicate 25-l volumes.…”
Section: Scientific Ethicsmentioning
confidence: 99%